2022
DOI: 10.1111/cts.13272
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically‐based pharmacokinetic model‐based translation of OATP1B‐mediated drug–drug interactions from coproporphyrin I to probe drugs

Abstract: The accurate prediction of OATP1B-mediated drug-drug interactions (DDIs) is challenging for drug development. Here, we report a physiologically-based pharmacokinetic (PBPK) model analysis for clinical DDI data generated in heathy subjects who received oral doses of cyclosporin A (CysA; 20 and 75 mg) as an OATP1B inhibitor, and the probe drugs (pitavastatin, rosuvastatin, and valsartan). PBPK models of CysA and probe compounds were combined assuming

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…We found that CL int ,all of CP‐I could be determined based primarily on the baseline‐to‐peak phase of its blood concentration through analysis of the clinical data where cyclosporin A, another strong inhibitor for OATP1B, was used as the OATP1B perpetrator. 29 CL int ,all in the present study could also be determined from the observed baseline‐to‐peak phase under the condition that the rate‐limiting step (uptake) of hepatic elimination was strongly inhibited by RIF. This subsequently enabled the determination of v syn from the steady‐state data without RIF.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…We found that CL int ,all of CP‐I could be determined based primarily on the baseline‐to‐peak phase of its blood concentration through analysis of the clinical data where cyclosporin A, another strong inhibitor for OATP1B, was used as the OATP1B perpetrator. 29 CL int ,all in the present study could also be determined from the observed baseline‐to‐peak phase under the condition that the rate‐limiting step (uptake) of hepatic elimination was strongly inhibited by RIF. This subsequently enabled the determination of v syn from the steady‐state data without RIF.…”
Section: Discussionmentioning
confidence: 75%
“…K i ,u,OATP could be primarily determined from the peak‐to‐baseline phase of the CP‐I blood concentration with the OATP1B inhibitor 29 . The quartiles for the estimated RIF K i ,u,OATP for CP‐I (using the reported model for CP‐I, 22 and the modified model for RIF) were similar between the analyses of the 2‐Dose‐RIF and the 3‐Dose‐RIF studies (0.044–0.055 μM and 0.046–0.060 μM, respectively; Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this preliminary analysis was made based on a very limited data set. A comprehensive analysis using a more diverse compound set is needed to determine whether Method 2 consistently yields a good performance for OATP1B-mediated DDI predictions for (Mochizuki et al, 2022a;Yoshikado et al, 2022).…”
Section: Clinical Relevance Of Trans-inhibition Mechanism To Oatp1b1-...mentioning
confidence: 99%